Multiperspectivity in lesson designs of history teachers: The role of schoolbook texts in the design of multiperspective history lessons - Marc Kropman (University of Newcastle, 2021)
Textbook narratives of a nation’s past often present a limited frame of reference, which impedes the aim of teaching history from multiple perspectives. This study aims to explore the use of multiperspectivity in teachers’ lesson designs for 10th grade students based upon a text that includes multiple perspectives (HP) (N=8) compared to a text that hardly includes multiperspectivity (LP) (N=10). The lesson designs were analyzed on multiperspectivity regarding aims, instruction, materials and learning activities, and also on actors, elements of scale, dimensions, historians interpretations and students’ perspectives. We found that different dimensions (for example, political, economic) were more often incorporated in the lesson designs based upon text HP, but that students’ perspectives were more often included in the designs based upon text LP. Only one fifth of the lesson designs reflected a high overall level of multiperspectivity. Nevertheless, text HP generated more multiperspectivity with respect to aims and instruction, dimensions, scale and historiography than text LP. Interviews with the teachers showed that the interpretation of the exam program – either a focus on learning historical reasoning or acquiring a chronological overview of knowledge – seemed decisive in the design of the lessons. This study calls for careful incorporating multiperspectivity in textbook by authors, and in their lessons by teachers who seek to do justice to multiple perspectives.